Climatic Vulnerability of El Mirador de Lambayeque Archaeological Complex (8th–11th Century AD): Morphometric Analyses of Digital Surface Models - Luigi Magnini; Pierdomenico Del Gaudio; Maria Ilaria Pannaccione Apa; Robert F. Gutierrez Cachay; Carlos E. Wester La Torre; Guido Ventura (Remote Sensing)
Archaeological sites may be damaged by natural phenomena related to climatic phenomena, such as wind, rain, and solar radiation. These phenomena are particularly intense in tropical areas subjected to the El Niño–Southern Oscillation. In these areas, the evaluation of the climatic vulnerability of archaeological sites represents a priority. El Mirador de Lambayeque Archaeological Complex (8th to 11th century CE) is located on the northern coast of Peru, an area exposed to intense rain and wind due to the El Niño–Southern Oscillation and solar radiation. A 16 cm resolution digital surface model (DSM) of the site was obtained from photogrammetric data. Selected morphometric parameters were extracted from this DSM with the aim of identifying the areas exposed to water flow or stagnation during rain, wind, and solar radiation. These parameters were elaborated with object-based image analyses and fuzzy logic methods to determine the climatic vulnerability of the archaeological site to these different phenomena. An estimate of the total vulnerability is also presented, along with an evaluation of the areas exposed to erosion and deposition due to long-term diffusive processes. The analytical approach applied to El Mirador de Lambayeque Archaeological Complex may be extended to other archaeological sites.